Investigation of temporal and spatial heterogeneities of the immune responses to Bordetella pertussis infection in the lung and spleen of mice via analysis and modeling of dynamic microarray gene expression data (2019)
Bordetella pertussis(B. pertussis) is the causative agent of pertussis, also referenced aswhooping cough. Although pertussis has been appropriately controlled by routine im-munization of infants, it has experienced a resurgence since the beginning of the 21stcentury. Given that elucidating the immune response to pertussis is a crucial factor toimprove therapeutic and preventive treatments, we re-analyzed a time course microarraydataset ofB. pertussisinfection by applying a newly developed dynamic data analysispipeline. Our results indicate that the immune response toB. pertussisis highly dynamicand heterologous across different organs during infection. Th1 and Th17 cells, which aretwo critical types of T helper cell populations in the immune response toB. pertussis, andfollicular T helper cells (TFHs), which are also essential for generating antibodies, might begenerated at different time points and distinct locations after infection. This phenomenonmay indicate that different lymphoid organs may have their unique functions duringinfection. Thesefindings provide a better understanding of the basic immunology ofbacterial infection, which may provide valuable insights for the improvement of pertussisvaccine design in the future.